The Effects of Catastrophic Thinking about Pain on Attentional Interference by Pain: No Mediation of Negative Affectivity in Healthy Volunteers and in Patients with Low Back Pain - G Crombez; C Eccleston; A Van den Broeck; B Van Houdenhove; L Goubert (Pain Research and Management)
BACKGROUND: Previous studies have shown that catastrophic thinking about pain enhances attentional interference in healthy volunteers.